Characterization of Flavonoids from Fern Cheilanthes Tenuifolia and Evaluation of Antioxidant, Antimicrobial and Anticancer Activities - Jarial, Rini; Shard, A.; Thakur, Sveta; Mimi Sakinah, A. M.; Zularisam, A. W.; Rezania, Shahabaldin; Kanwar, S. S.; Singh, L. (King Saud University, 2017)
The present study is designed to identify various bioactive flavonoid compounds from the methanolic fern extract (MFE) of Cheilanthes tenuifolia. Flavonoids derived from C. tenuifolia (fern) possess potent anti-cancerous, anti-bacterial, anti-oxidant activities that are responsible for their chemo-preventive potential against selected bacterial panel. A preparative column chromatography with a column Sephadex LH-20 was used to isolate and purify flavonoids from C. tenuifolia. Their structure and chemical bonds were identified by using Nuclear Magnetic Resonance (NMR) spectroscopy and Fourier Transform-Infra Red Spectroscopy (FTIR). Two flavonoids were identified as rutin (2.8 mg) and quercetin (3.34 mg) from 100 g of C. tenuifolia. The minimum inhibitory concentration (MIC) values of (2.25 and 0.45 mg/ml) were obtained in purified flavonoids against Staphylococcus aureus and Enterobacter sp., respectively. The two flavonoids (Rutin and quercetin) showed significant in vitro anti-oxidant activity; in this regard, the 2, 2-diphenyl-1-picrylhydrazyl (DPPH) scavenging potential of quercetin (86.1%) was higher than that of rutin (73.2%). However, for human hepatoma HepG2 and human carcinoma HeLa cells, quercetin exhibited high anti-cancer activity than rutin. The purified compounds (rutin and quercetin) with having great potential of free radical inactivator in HepG2 cells. The results suggest that MFE of C. tenuifolia could potentially be employed in traditional medicine as they are rich in compounds with anti-oxidant, anti- microbial and anti-cancer properties.